Surface heating of wire plasmas using laser-irradiated cone geometries - Green, J; Lancaster, K; Akli, K; Gregory, C; Beg, F; Chen, SN; Clark, D; Freeman, R; Hawkes, S; Hernandez-Gomez, C; Habara, H; Heathcote, R; et al. (2007)
Petawatt lasers can generate extreme states of matter, making them unique tools for high-energy-density physics. Pressures in the gigabar regime can potentially be generated with cone-wire targets when the coupling efficiency is high and temperatures reach 2-4keV (ref.1). The only other method of obtaining such gigantic pressures is to use the megajoule laser facilities being constructed (National Ignition Facility and Laser MégaJoule). The energy can be transported over surprisingly long distances but, until now, the guiding mechanism has remained unclear. Here, we present the first definitive experimental proof that the heating is maximized close to the wire surface, by comparison of interferometric measurements with hydrodynamic simulations. New hybrid particle-in-cell simulations show the complex field structures for the first time, including a reversal of the magnetic field on the inside of the wire. This increases the return current in a spatially separated thin layer below the wire surface, resulting in the enhanced level of ohmic heating. There are a significant number of applications in high-energy-density science, ranging from equation-of-state studies to bright, hard X-ray sources, that will benefit from this new understanding of energy transport.